2021
DOI: 10.1007/s00500-021-05970-4
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Speech Steganography System using SS-RDWT with IPDP-MLE approach

Abstract: In the last two decades, it has been observed that there have been remarkable advancements in digital media communication. It has lots of advantages and business potential as it needs no physical media or transport. However, digital media can also create several big problems for media owners due to unauthorized use, ease of replication, plasticity, and equivalence of works in digital form. The possible solution is to secure digital media by cover writing which can also referred as steganography. Therefore, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Fecal incontinence (FI) is generally defined as the uncontrolled passage of feces for a duration of at least 3 months in an individual who previously had control. 1,2 The prevalence of FI varies widely depending on the specific definition used and the population surveyed, ranging between 1.4% and 18% in women. [3][4][5][6][7][8] A study of bowel function in a primary care network found the incidence of FI to be 12.5%, with many patients reporting moderate to severe FI (Vaizey score more than 8).…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Fecal incontinence (FI) is generally defined as the uncontrolled passage of feces for a duration of at least 3 months in an individual who previously had control. 1,2 The prevalence of FI varies widely depending on the specific definition used and the population surveyed, ranging between 1.4% and 18% in women. [3][4][5][6][7][8] A study of bowel function in a primary care network found the incidence of FI to be 12.5%, with many patients reporting moderate to severe FI (Vaizey score more than 8).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…5 The management of FI is challenging and needs to be individualized according to the severity of symptoms, cause, and coexisting pathology. 2,[13][14][15][16][17] Aside from conservative and supportive measures, several surgical interventions are available to treat FI with variable efficacy. This practice guideline reviews the medical and surgical options currently available for the management of patients with FI.…”
Section: Statement Of the Problemmentioning
confidence: 99%